The Relationship Between Work Posture And Repetitive Movements With Musculoskeletal Disorders (MSDs) Among Management Department Employees At Prof. Dr. H. M. Chatib Quzwain Regional General Hospital, Sarolangun - Alda Deninta Regina; Budi Aswin; Hendra Dhermawan Sitanggang; Muhammad Syukri (International Journal of Health Engineering and Technology, 2026)
Musculoskeletal Disorders (MSDs) are musculoskeletal system disorders affecting muscles, joints, tendons, and supporting tissues that may arise due to non-ergonomic working postures and repetitive occupational activities. Hospital management employees are considered a high-risk group for MSDs because their work predominantly involves prolonged sitting and extensive computer use. This study was conducted to examine the association between work posture and repetitive movements with the occurrence of Musculoskeletal Disorders (MSDs) among management employees at Prof. Dr. H.M. Chatib Quzwain Regional Hospital, Sarolangun. An analytical observational study with a cross-sectional design was employed. The study involved 31 respondents selected through purposive sampling. Data were obtained using the Nordic Body Map (NBM) questionnaire to identify MSD complaints, the Rapid Upper Limb Assessment (RULA) method to evaluate work posture, and direct observation to assess repetitive work activities. Data analysis was carried out using univariate and bivariate techniques with the Chi-Square test at a 95% confidence level. The findings revealed that 58.1% of respondents experienced moderate MSD complaints, 80.6% demonstrated high-risk work postures, and 54.8% engaged in repetitive work activities categorized as risky. The bivariate analysis showed that work posture was not significantly related to MSD occurrence (p = 0.656), whereas repetitive movements had a significant association with MSDs (p = 0.022). These findings indicate that repetitive work activities play a more substantial role in the development of MSDs than work posture among hospital management employees. Therefore, the implementation of ergonomic workplace practices and adequate rest periods is recommended to minimize the risk of MSDs.